(3HOGjI GdgOGjIs - (3GdYGedj, GdoMQ, GdMQ GdYGedj, eMeO Hf GdMSf Hf Ydj, J (B1104(3g` (B1692(3es ((3QGTO Hf CeGf Hf SGdes)
(3ChdgG (B:s
(3ChdgG(B: (3SHMGfg hhMOGfjJg hYOdg hYdeg (B...(3aUd aj GdejGg(B: (3dG JLhR GdWgGQI HGdeGA GdfLS agh eG JZjQ HGdfLGSIs
(3BNQgG (B:s
(3BNQgG(B: (3hGdeMQeGJ CdkaG hCQHY eFI hKeGfjI hCQHYjf, jchf GdeLehY KdGK BdGa EdG SHYI YTQ JbQjkHG dCf aj HYVgG JOGNkdG hJcQGQ jSjQGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 90s
(3GdPQjYI, L (B3: 33 - 34s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis